2019
DOI: 10.4315/0362-028x.jfp-18-607
|View full text |Cite
|
Sign up to set email alerts
|

Occurrence and Phenotypic and Molecular Characterization of Antimicrobial Resistance of Salmonella Isolates from Food in Tunisia

Abstract: Salmonella is a leading cause of foodborne diseases worldwide. The use of antibiotics in food-producing animals may contribute to the development of antimicrobial resistance in nontyphoidal Salmonella. The development of resistance to potent antimicrobials such as fluoroquinolones and extended-spectrum β-lactamases is a significant public health problem. The present study was conducted to examine the occurrence and antimicrobial resistance of Salmonella isolates obtained from food samples. Salmonella was cultu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 54 publications
2
7
0
Order By: Relevance
“…Carbapenem resistance, mainly among Gram-negative pathogens, is an ongoing public health problem of global dimensions. This type of antimicrobial resistance, especially when mediated by transferable carbapenemase-encoding genes, is spreading rapidly, causing serious outbreaks and dramatically limiting treatment options [55].In addition, the results of our study corroborate those of Ben Hassena et al (2019) [56], who reported the emergence of multidrug-resistant Salmonella strains isolated from food with decreased susceptibility to fluoroquinolones and third-generation cephalosporin in Tunisia. Then, our findings show the importance of embracing the "One Health" approach that was promulgated by the World Health Organization in its action plan against antimicrobial resistance, which mobilizes various actors in three main sectors: animal husbandry, environment, and human health.…”
Section: Discussionsupporting
confidence: 83%
“…Carbapenem resistance, mainly among Gram-negative pathogens, is an ongoing public health problem of global dimensions. This type of antimicrobial resistance, especially when mediated by transferable carbapenemase-encoding genes, is spreading rapidly, causing serious outbreaks and dramatically limiting treatment options [55].In addition, the results of our study corroborate those of Ben Hassena et al (2019) [56], who reported the emergence of multidrug-resistant Salmonella strains isolated from food with decreased susceptibility to fluoroquinolones and third-generation cephalosporin in Tunisia. Then, our findings show the importance of embracing the "One Health" approach that was promulgated by the World Health Organization in its action plan against antimicrobial resistance, which mobilizes various actors in three main sectors: animal husbandry, environment, and human health.…”
Section: Discussionsupporting
confidence: 83%
“…The resistance of Salmonella spp. to critically important antimicrobials, such as fluoroquinolones and extendedspectrum cephalosporins, is a significant public health concern, threatening the efficiency of antimicrobial agents (Campos et al, 2018;Hassena et al, 2019). High rates of Salmonella spp.…”
Section: Resultsmentioning
confidence: 99%
“…Salmonella spp. is among the most frequent causes of foodborne illnesses and the growing presence of MDR strains is a further cause of concern (Franco et al ., 2015 ; Hassena et al ., 2019 ; Parvin et al ., 2020 ; Proietti et al ., 2020 ; Peruzy et al ., 2020 ; Gargano et al ., 2021 ; Lauteri et al ., 2022 ). Between 2019 and 2021, 40 strains of Salmonella spp.…”
Section: Discussionmentioning
confidence: 99%